ANALISIS YURIDIS PERJANJIAN KEAGENAN DALAM PEMASARAN CRUDE PALM OIL (CPO) ANTARA PT PERKEBUNAN NUSANTARA IV (PERSERO) DENGAN PT KHARISMA PEMASARAN BERSAMA NUSANTARA - STELLA STELLA STELLA (PREMISE LAW JURNAL, 2017)
Abstract Agency is a representative made by the power transfer based on Article 1354 of the Civil Codes as a representative which is based on an agreement such as the power transfer. An agency agreement has 3 main parties; namely, the principle, agent and the third party. The state-owned enterprise producing natural resources, PT Perkebunan Nusantara IV (PTPN IV), has made an agency agreement with PT KPBN (PT Kharisma Pemasaran Bersama Nusantara) to market commodity such as CPO (Crude Palm Oil) and tea. The research result shows that the validity requirements of the agency agreement are based on Article 1320 of the Civil Codes. The agency agreement between PTPN IV and PT KPBN is formed fairly according to the law due to equal position in the bargaining or trading among the parties’ rights and liability. They are liable for all contracts and the contents which have been agreed before. In case of defaults among the parties, the disputes are settled by negotiations among all parties. If the settlement is not reached by the negotiation, it will be brought to BANI (Indonesia National Arbitrary Institution) and/or the local court. Keywords: Agency Agreement, Marketing, Crude Palm Oil